The prohibition and requirement the corruption for the Malikis -applied study on sales- - Qharaibeh, Enas (Jordan Journal of Islamic Studies, 2023)
The study explained the linguistic and idiomatic meaning of prohibition and corruption and explained the views of Maliki scholars on the issue of requiring the prohibition of corruption, and the jurisprudential applications on this issue in sales, the study concluded that the prohibition requires corruption in worship, but in transactions it returns to the state of which it is prohibited. The prohibition was in the meaning in the prohibited, or for its own sake, or to describe it that requires corruption, and if it wasn’t in meaning of the prohibited, it differs on two matters: if the prohibition against the right of God requires corruption, and if it is to the right of a people it does not require corruption, and the corrupt sale is proven by the Malikis the suspicion of the Property in four things: the change of markets, the change of the Sold or destruction, or the suspension of the right of others to it.